The Role of Transformational Leadership on Organizational Citizenship Behavior of Elementary School Teachers in Bekasi Regency - Suharyat, Yayat; Ariawan, Ariawan; Lee Cameliana, Dina Asrian; Kamar, Karnawi; Zahruddin, Achmad; Barrulwalidin, Barrulwalidin (Universitas Pendidikan Indonesia, 2023)
In reality, Organization Citizenship Behavior in an institution is not as expected. However, the contrary occurred at the Integrated Islamic Elementary School in Bekasi Regency that teachers and staff have a spectrum of abilities and the potential to advance the institution. This research identified and analyzed (1) the role of the principal in improving teachers behavior through transformational leadership, and (2) the inhibiting and supporting factors in improving good teachers behavior and attitudes at the Integrated Islamic Elementary School in Bekasi Regency, Indonesia. The research used a qualitative method with a phenomenological approach. The principal, representatives, and teachers were informants to obtain the necessary data. The findings showed that the implemented Organizational Citizenship Behavior embodied sincerity, mutual help, brotherhood, and seriousness. However, it still needed improvement to achieve maximum teachers performance in carrying out the task of educating, guiding, training, and directing the students. One of the obstacles in implementing transformational leadership was that several teachers underestimated this program. This research has an implication that Organizational Citizenship Behavior in an institution can be realized if a leader implements a transformational leadership system.